Enabling large-scale integration of electric bus fleets in harsh environments: Possibilities, potentials, and challenges - Salman Harasis (21841988) (2024)
This paper presents a comprehensive and detailed investigation of electric bus transit systems, focusing on their feasibility in harsh environmental areas. The aspects that combine economics, operation, long-term performance, and reliability are all addressed and discussed in both short and long-term horizons. This work covers most of the “important to consider” criteria, compares the strategies applied in E-bus energy management, and recommends the best practices to follow in the presence of many system variables. Due to the significant impact of the ambient temperature, characterizing the battery performance under hot ambient temperatures is performed considering the existing Li-ion battery technologies. Moreover, the grid impact of large-scale charging systems is identified and classified by identifying the factors affecting the grid hosting capacity and permissible interaction levels. This work includes developing a comprehensive picture of the state of the art, emphasizing the gaps found in the literature, and proposing new venues for future research that help address the identified issues to enable reliable E-transportation plans. Other Information Published in: Energy License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.energy.2024.131564